Pseudo-Temporal Analysis of Single-Cell RNA Sequencing Reveals Trans-Differentiation Potential of Greater Epithelial Ridge Cells Into Hair Cells During Postnatal Development of Cochlea in Rats - Chen, Jianyong; Gao, Dekun; Chen, Junmin; Hou, Shule; He, Baihui; Li, Yue; Li, Shuna; Zhang, Fan; Sun, Xiayu; Jin, Yulian; Sun, Lianhua; Yang, Jun (Frontiers in Molecular Neuroscience, 2022)
The hair cells of the cochlea play a decisive role in the process of hearing damage and recovery, yet knowledge of their regeneration process is still limited. Greater epithelial ridge (GER) cells, a type of cell present during cochlear development that has the characteristics of a precursor sensory cell, disappear at the time of maturation of hearing development. Its development and evolution remain mysterious for many years. Here, we performed single-cell RNA sequencing to profile the gene expression landscapes of rats' cochlear duct from P1, P7, and P14 and identified eight major sub-types of GER cells. Furthermore, single-cell trajectory analysis for GER cells and hair cells indicated that among the different sub-types of GER, four sub-types had transient cell proliferation after birth and could trans-differentiate into inner and outer hair cells, and two of them mainly trans-differentiated into inner hair cells. The other two sub-types eventually trans-differentiate into outer hair cells. Our study lays the groundwork for elucidating the mechanisms of the key regulatory genes and signaling pathways in the trans-differentiation of GER cell sub-types into hair cells and provides potential clues to understand hair cell regeneration.